Distribution of O-Acetylated Sialic Acids among Target Host Tissues for Influenza Virus - Brian R. Wasik (American Society for Microbiology, 2017)
ABSTRACT Sialic acids (Sias) are important glycans displayed on the cells and tissues of many different animals and are frequent targets for binding and modification by pathogens, including influenza viruses. Influenza virus hemagglutinins bind Sias during the infection of their normal hosts, while the encoded neuraminidases and/or esterases remove or modify the Sia to allow virion release or to prevent rebinding. Sias naturally occur in a variety of modified forms, and modified Sias can alter influenza virus host tropisms through their altered interactions with the viral glycoproteins. However, the distribution of modified Sia forms and their effects on pathogen-host interactions are still poorly understood. Here we used probes developed from viral Sia-binding proteins to detect O-acetylated (4-O-acetyl, 9-O-acetyl, and 7,9-O-acetyl) Sias displayed on the tissues of some natural or experimental hosts for influenza viruses. These modified Sias showed highly variable displays between the hosts and tissues examined. The 9-O-acetyl (and 7,9-) modified Sia forms were found on cells and tissues of many hosts, including mice, humans, ferrets, guinea pigs, pigs, horses, dogs, as well as in those of ducks and embryonated chicken egg tissues and membranes, although in variable amounts. The 4-O-acetyl Sias were found in the respiratory tissues of fewer animals, being primarily displayed in the horse and guinea pig, but were not detected in humans or pigs. The results suggest that these Sia variants may influence virus tropisms by altering and selecting their cell interactions. IMPORTANCE Sialic acids (Sias) are key glycans that control or modulate many normal cell and tissue functions while also interacting with a variety of pathogens, including many different viruses. Sias are naturally displayed in a variety of different forms, with modifications at several positions that can alter their functional interactions with pathogens. In addition, Sias are often modified or removed by enzymes such as host or pathogen esterases or sialidases (neuraminidases), and Sia modifications can alter those enzymatic activities to impact pathogen infections. Sia chemical diversity in different hosts and tissues likely alters the pathogen-host interactions and influences the outcome of infection. Here we explored the display of 4-O-acetyl, 9-O-acetyl, and 7,9-O-acetyl modified Sia forms in some target tissues for influenza virus infection in mice, humans, birds, guinea pigs, ferrets, swine, horses, and dogs, which encompass many natural and laboratory hosts of those viruses.